Implementation Of Safety Equipment Above Kmp. Nusa Penida, Kmp. Nusa Bhakti And Kmp. Nusa Sakti Operates In Padangbai Port - Noor Sulistiyono; Siti Nurlaili Triwahyuni; Keni Sri Darma Putri (IWTJ : International Water Transport Journal, 2022)
The Padangbai Ferry terminal is a port managed by the BPTD XII Bali and West Nusa Tenggara. The Padangbai ferry terminal serves 2 routes with 26 Ro-Ro ships in operation. One of the important components in ferry transportation is safety. Safety is shown not only to service users but also to ship crews. On ships operating at the Padangbai Ferry Terminal, there are many damaged safety equipment including life jackets, lifebuoys, lifeboats and Fire protection (fire Extinguisher) the number of safety equipment that does not match the ship's needs based on Safety of Life at Sea (SOLAS). The condition and number of safety equipment and Fire protection must be considered both in terms of the appropriateness of the tools and fittings so that in an emergency the existing safety equipment can be used properly as a form of carrying out the safety aspects of passengers on board. The number and condition of safety equipment and Fire protection that is not in accordance with the needs can endanger the safety of the lives of passengers if an accident occurs. The number of safety equipment must be able to accommodate the number of passengers and crew on board and fire extinguishers must be in good condition so that they can be used in a fire emergency.